The (Domestic) Enforcement of AU International Economic Law Instruments: Exploring the Desirability of Direct Effect - Simo, Regis Yann (The Emergent African Union Law: Conceptualization, Delimitation, and Application, 2021)
This chapter deals with the principle of direct effect as applied in European Union law and explores its suitability in the enforcement of African Union (AU) legal instruments, notably those setting up the African Continental Free Trade Area (AfCFTA). What motivates the issue of direct effect is the noted reticence of African countries to litigate trade matters between themselves despite the existence of provisions of regional trade treaties creating courts of justice which give standing to Member States. Therefore, it surveys the avenues through which natural and legal persons can uphold their rights stemming from AfCFTA treaties thus contributing to treaty interpretation and increasing security and predictability. Currently, the AfCFTA Dispute Settlement Protocol, modelled after the WTO, does not allow such a possibility, contrary to rights acquired by natural and legal persons before some African Regional Economic Communities (RECs) courts. Nevertheless, this chapter finds that carving out access of natural and legal persons to AfCFTA proceedings may not always work as intended since there are other ways to bypass these obstacles. These loopholes could be the gateway through which direct effect will develop and become a principle of AU law broadly speaking. These gaps further complement this chapter’s suggestions to explore amending the AfCFTA legal instruments, even though its dispute settlement system is yet to be tested, in order to match the standing that natural and legal persons have acquired under the RECs, which, in fine, are building blocs towards achieving the AfCFTA and, eventually, the African Economic Community.
Keywords: AfCFTA; Africa; Direct effect; International Economic Law; International Law; International Trade Law; Regional courts; Regional integration

Chapter II: The Arbitrator and the Arbitration Procedure, An Arbitrator’s Imperative – How to Avoid Disappointing the Parties, Preventing Surprises and Enabling Efficient and Progressive Arbitral Proceedings - Welser, Irene; Mimnagh, Samuel (Austrian Yearbook on International Arbitration, 2021)